Dynamics and correlation of serum cortisol and corticosterone under different physiological or stressful conditions in mice. - Shuai Gong; Yi-Long Miao; Guang-Zhong Jiao; Ming-Ju Sun; Hong Li; Juan Lin; Ming-Jiu Luo; Jing-He Tan (PLoS ONE)
Although plasma corticosterone is considered the main glucocorticoid involved in regulation of stress responses in rodents, the presence of plasma cortisol and whether its level can be used as an indicator for rodent activation of stress remain to be determined. In this study, effects of estrous cycle stage, circadian rhythm, and acute and chronic (repeated or unpredictable) stressors of various severities on dynamics and correlation of serum cortisol and corticosterone were examined in mice. A strong (r = 0.6-0.85) correlation between serum cortisol and corticosterone was observed throughout the estrous cycle, all day long, and during acute or repeated restraints, chronic unpredictable stress and acute forced swimming or heat stress. Both hormones increased to the highest level on day 1 of repeated-restraint or unpredictable stresses, but after that, whereas the concentration of cortisol did not change, that of corticosterone showed different dynamics. Thus, whereas corticosterone declined dramatically during repeated restraints, it remained at the high level during unpredictable stress. During forced swimming or heat stress, whereas cortisol increased to the highest level within 3 min., corticosterone did not reach maximum until 40 min. of stress. Analysis with HPLC and HPLC-MS further confirmed the presence of cortisol in mouse serum. Taken together, results (i) confirmed the presence of cortisol in mouse serum and (ii) suggested that mouse serum cortisol and corticosterone are closely correlated in dynamics under different physiological or stressful conditions, but, whereas corticosterone was a more adaptation-related biomarker than cortisol during chronic stress, cortisol was a quicker responder than corticosterone during severe acute stress.